Imperative of corporate governance on industry's profitability: An empirical study of privatized cement industry in Nigeria - GOMBE, Bappayo Masu; ALIERO, Ibrahim H. (Turkish Economic Review, 2021)
Abstract. The study investigates the imperative of corporate governance on profitability of privatized cement industry in Nigeria. The variables studied were Rate of Returns as dependent variables and fourteen Corporate Governance proxies as independent variables. Data was collected from secondary sources, and the statistical tools employed in the Methodology were descriptive statistics and Pooled OLS regressions. The study aimed at bridging literature gap on studies that relate corporate governance and privatization policy in Nigeria. The results suggest that, no remarkable improvement of profitability post privatization due to challenges of exogenous factors such as macroeconomic environment instability and weak private sector. The industry witnessed changes in corporate governance such as adopting effective cost management and proactive business strategies, exposure to competition, withdrawal of Government subsidy and special grant post privatisation. Board Size and Workforce have positive and significant impact on Cement industry’s profitability, while, State Ownership, Institutional Ownership, Minority ownership, Percentage of Executive Directors and Privatization with time have negative and significant impact on company’s profitability. Conversely, Foreign Investors, Percentage of Non-Executive Directors and Percentage of Management Staff have positive and insignificant impact on the Cement industry’s profitability. Thus, it will be pertinent to conclude that the result has accepted Alternative Hypothesis that corporate governance has significant impact on the Cement industry’s performance (AROA), despite the challenges of microeconomic environment instability. The study recommends that, Government needs to stabilize macroeconomic environment and strengthen private sector. The Cement Industry needs to ensure right procedure of the selection of Non-Executive Directors, create incentive for foreign investor participation, ensure Payment of dividend, less government interference and accountability. Mechanisms such as efficient and independent audit committee, competent executive directors and professional management team need to be put in place to address the negative and insignificant impact of management staff on the industry. Keywords. Corporate governance, Profitability, Privatization, Cement industry. JEL. C01, C50, E10, E60, F02, F30, F41.